A Review of Abul Kalam Azad’s Commentary on the Qur'an, “Tarjumān Al-Qur’ān” - Muhammed Rashid Jalaly (Penerbit Hellow Pustaka, 2024)
Since its earliest revelation, the Qur'an has continued to serve as Muslims' primary source of intellectual inspiration and contemplation. With the help of the Qur'an, the Prophet helped his companions modify their perspectives. In addition to reciting the Qur'an to his companions, the Prophet also used to explain its meaning to them. The guidelines for reading the Qur'an were created to enlighten future generations on how their forefathers arrived at a certain interpretation so that they wouldn't overlook the problems unique to their own eras. Among the distinguished Qur'anic exegetes that India has produced, Abul Kalam Azad has a noteworthy position. It is an Urdu commentary on the Qur'an written by Azad between 1915 and 1945, a turbulent time when he was imprisoned by the British government multiple times for extended periods of time. In the lengthy list of his writings on many themes, his Tarjumān al-Qur’ān is actually his Magnum Opus. The most notable contribution to Islamic scholarship made by Abul Kalam Azad was Tarjumān al-Qur’ān, a sincere endeavour to explain the message as it was understood by the Prophet Muhammad's (PBUH) followers’ during his lifetime. According to him, commentators in more recent times have diverted from the previous accurate understanding under the influence of foreign culture and ideas. It is more detailed than a simple translation, but it is by no means complex. One of the greatest translations of the Quran was considered by Arabic academics to be the original